Thioredoxin from the Indianmeal moth Plodia interpunctella: cloning and test of the allergenic potential in mice. - Elisabeth Hoflehner (Public Library of Science (PLoS), 2012)
Background/objective The Indianmeal moth Plodia interpunctella is a highly prevalent food pest in human dwellings, and has been shown to contain a number of allergens. So far, only one of these, the arginine kinase (Plo i 1) has been identified. Objective The aim of this study was to identify further allergens and characterise these in comparison to Plo i 1. Method A cDNA library from whole adult P. interpunctella was screened with the serum of a patient with indoor allergy and IgE to moths, and thioredoxin was identified as an IgE-binding protein. Recombinant thioredoxin was generated in E. coli, and tested together with Plo i 1 and whole moth extracts in IgE immunoblots against a large panel of indoor allergic patients' sera. BALB/c mice were immunised with recombinant thioredoxin and Plo i 1, and antibody production, mediator release from RBL cells, T-cell proliferation and cytokine production were measured. Result For the first time a thioredoxin from an animal species was identified as allergen. About 8% of the sera from patients with IgE against moth extracts reacted with recombinant P. interpunctella thioredoxin, compared to 25% reacting with recombinant Plo i 1. In immunised BALB/c mice, the recombinant allergens both induced classical Th2-biased immune responses such as induction IgE and IgG1 antibodies, upregulation of IL-5 and IL-4 and basophil degranulation. Conclusion Thioredoxin from moths like Plo i 1 acts like a classical Type I allergen as do the thioredoxins from wheat or corn. This clearly supports the pan-allergen nature of thioredoxin. The designation Plo i 2 is suggested for the new P. interpunctella allergen.